Eletroquímica medicinal de quinonas: integração entre eletroquímica, atividades biológicas, interação com DNA e métodos computacionais - Paiva, Yen Galdino de (2016)
Redox activation in Medical Chemistry is very important. Electrochemical studies provide termodynamic and kinetic parameters of bioactive compounds, under different conditions that may be related to their biological activity in living cells. Quinones are considered privileged scaffolds in medicinal chemistry due to their structural properties and biological activities against pathogenic protozoa and many cancer cells lines. The present thesis focused in the investigation of more than 40 hybrid quinones and their precursors, with different substitutions organized in classes according to the quinone structure and substitution pattern. Electrochemical, fluorimetric and spectrophotometric techniques, computational studies and biological assays were performed. Electrochemical techniques have been used extensively to provide insights into the modes of action of drugs. Although quinones reduction studies reveal a complex mechanism strongly dependent on the reaction media, these compounds displayed a typical electrochemical behavior in aprotic media (DMF/TBAP or TBAPF6). The dsDNA biosensor and ssDNA experiments were used to analyse the positive and direct interaction of some quinones with DNA and oxygen studies showed the formed radical anions interact with oxygen. Additionally, biological assays and computational studies were performed, in order to try understanding the molecular mechanism of biological action of these compounds and to make correlations structure/electroactivity/biological activity. Among biological assays, the protecting effect of some quinones against lipid peroxidation and activity on biofilm-producing bactéria were performed. From biological data in different câncer cell lines and/or trypomastigote forms of Trypanosoma cruzi, comparison with electrochemical parameters, obtained in aprotic medium, was held, with a positive trend: there is an ideal range for reduction activation of the quinones. If the quinones are very easily reduced, they turn less active, as well as when they are reduced too negatively (more negative potentials), their biological activity is lost. These results and the positive correlations can inspire the design of the next- generation of bioactive quinones, in terms of increased selectivity and efficiency against several diseases, mainly those biochemically connected to oxidative stress and biological alkylation.